Low Reynolds Number Mass Transfer in Packed Beds of Cylindrical Particles - Kumar S.; Upadhyay S.N.; Mathur V.K. (My University, 2025)
Mass transfer coefficients from dumped packed beds of cylindrical pellets of benzoic acid to water and 60% aqueous propylene glycol solution are measured in the NRe range of 0.01 to 600. Conventional correlations in terms of mass transfer factor and Reynolds number as well as asymptotic relations (Karabelas et al., 1971) In terms of Grashof, Reynolds, Schmidt, and Sherwood numbers are presented. © 1977, American Chemical Society. All rights reserved.